Snaps to Connect Coaxial and Microstrip Lines in Wearable Systems - Tiiti Kellomäki (International Journal of Antennas and Propagation)
Commercial snaps (clothing fasteners) can be used to connect a coaxial cable to a microstrip line. This is useful in the context of wearable antennas, especially in consumer applications and disposable connections. The measured S-parameters of the transition are presented, and an equivalent circuit and approximate equations are derived for system design purposes. The proposed connection is usable up to 1.5 GHz (10 dB return loss condition), and the frequency range can be extended to 2 GHz if a thinner, more flexible coaxial cable is used.